Pengembangan Bahan Ajar Berbasis Agumented Reality pada Matakuliah Kebijakan Moneter dan Kebanksentralan : Development of Augmented Reality-Based Teaching Materials for Monetary Policy and Central Banking Courses - Silaban, Putri Sari M J; Putriku, Aurora Elise; Yuni, Revita; Hasibuan, Novita Indah (ITScience (Information Technology and Science), 2024)
Teaching materials play an essential role in the learning process, one of which is to promote independent learning. Teaching materials provide students with the opportunity to learn on their own. Graduate achievement is required for this course. Students must be able to understand economic problems, relevant monetary policies, and steps taken by central banks to address economic problems, especially the implementation of monetary policy by central banks. The scope of discussion includes an introduction, money supply, money demand theory, Bank Indonesia as a central bank, and monetary policy. Innovative teaching materials and independent learning spaces are needed to facilitate this goal for students. Teaching materials are made in the form of three-dimensional augmented reality. This study adapts the ADDIE development model. Due to time constraints, this study did not conduct a final evaluation before the formative evaluation stage. Three validators have verified the augmented reality-based learning materials, and the results show that the learning materials are helpful but need to be modified. A study was conducted on a large-scale group of 25 students in the fifth semester who were selected randomly. Learning materials are effective in the learning process based on test results.